2013
DOI: 10.1093/infdis/jit632
|View full text |Cite
|
Sign up to set email alerts
|

Selected Vaginal Bacteria and Risk of Preterm Birth: An Ecological Perspective

Abstract: We examined the community ecology of vaginal microbial samples taken from pregnant women with previous preterm birth experience to investigate whether targeted pathogenic and commensal bacteria are related to risk of preterm birth in the current pregnancy. We found a significant correlation between the community structure of selected bacteria and birth outcome, but the correlation differed among self-reported racial/ethnic groups. Using a community ordination analysis, we observed infrequent co-occurrence of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 36 publications
0
35
1
1
Order By: Relevance
“…In contrast, a recent Brussels study (28) of nearly 2000 pregnancies found Ureaplasma species to be a significant risk for preterm birth, and a commensurate risk of preterm birth was associated with abnormal flora, but only if Ureaplasma species was culture positive. These variable results may be related to differences in vaginal ecologies as recently described in studies of high-risk pregnancies (29,30). …”
Section: Discussionmentioning
confidence: 80%
“…In contrast, a recent Brussels study (28) of nearly 2000 pregnancies found Ureaplasma species to be a significant risk for preterm birth, and a commensurate risk of preterm birth was associated with abnormal flora, but only if Ureaplasma species was culture positive. These variable results may be related to differences in vaginal ecologies as recently described in studies of high-risk pregnancies (29,30). …”
Section: Discussionmentioning
confidence: 80%
“…Romero et al detected no difference in the microbial profiles of women who subsequently delivered term or preterm, whereas others reported differences in the prevalence and abundance of organisms such as Leptotrichia / Sneathia (bacteria associated with vaginosis), Mobiluncus spp., and Mycoplasma spp. in the vaginal microbiomes of women who delivered preterm . However, no comparative study has characterized the vaginal microbiome of pregnant women in Korea.…”
Section: Introductionmentioning
confidence: 79%
“…Total bacterial load was estimated using a broad coverage universal bacterial primer for the 16S rrn gene. Primer sequences and conditions used for individual taxa were reported previously 13 . The limit of detection was 100 copies and readings lower than the limit were considered negative.…”
Section: Methodsmentioning
confidence: 99%